Survey on the Effectiveness of the Online Learning Process Due to the Coronavirus (Covid-19) Pandemic in Floor Gymnastics Course - Kurniawan, Ari Wibowo; Hasan, Ahmad Nur Hamzah (Journal Coaching Education Sports, 2021)
The purpose of this study was to determine the level of effectiveness of the online learning process in floor gymnastics for students of 2019 Physical Education, Health and Recreation, State University of Malang. This study used a quantitative descriptive research design with a survey method. The sample taken in this study is 60% of the total population, namely 139 students of PJKR 2019. Data collection uses a questionnaire instrument based on google form, with five indicators in it (student interest, attractiveness, benefits, technology, interactive quality). The results of this study can be concluded that online learning in floor gymnastics courses can be declared quite effective for PJKR 2019 students. This is evidenced by the results of research that have been carried out with five indicators, as follows: 99 students out of 139 PJKR 2019 students stated that they were quite interested follow online learning in floor gymnastics with a percentage of 71.22%; 59% or 82 students stated that online learning is quite interesting to do; online learning was also stated to be quite beneficial for PJKR 2019 students with a percentage of 58% or 81 students answered quite useful; on the technology indicator, the results were 79% in the medium category; online learning is stated to be quite interactive in floor gymnastics subjects with a percentage of 63.31%.